Fungsi Agama dalam Grup WhatsApp Lansia GKI Tegalrejo: Sebuah Studi Lived Religion Digital - Widhipangreksa, Raharjo; Lattu, Izak Yohan Matriks; Prayitno, Iky Sumarthina P. (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the functions of religion in the religious experiences of elderly members involved in a religious WhatsApp group at GKI Tegalrejo, Salatiga. This study employs a qualitative descriptive–interpretative approach supported by descriptive quantitative data. The participants consisted of 12 elderly individuals aged 60–75 who had been actively involved in the religious WhatsApp group for at least six months. Data were collected through a 1–4 scale questionnaire to map the intensity of digital religious experiences, as well as semi-structured interviews to explore the meanings of those experiences. The findings indicate that the WhatsApp media group functions as a digital religious space that primarily strengthens the social and emotional functions of religion, such as a sense of togetherness, emotional support, and the presence of a faith community. These findings suggest that digital media function not only as communication tools but also as a medium of religious experience that is relevant to the lives of the elderly today.